Shifting Positionalities in a Time of COVID-19: The Transnational Public Health Doctor and Ethnographer - Saleh, Sepeedeh (Frontiers in Sociology, 2021)
Ethnographic research is characterised by in-person engagement with individuals and groups within a social setting, usually over an extended timeframe. These elements provide valuable insights which cannot be gained through other forms of research. In addition, such levels of involvement in “the field” create complex, shifting researcher-participant relationships which themselves shape the course of the project and its findings. The COVID-19 pandemic disrupted many research projects, but impacts on ethnographic research, with its emphasis on physical presence in the field and interpersonal relationships, reveals much about these key elements of our praxis. I discuss how the pandemic influenced the progress of an ethnographic research project, based in Malawi, including consideration of how, as lead for the project, my clinical/“public health” positionalities interacted with relationships in the village and the arrival of COVID-19 in Malawi. This account reveals shifting intersubjectivities of researchers and participants as the pandemic brought changes in the nature of the engagement, from ethnographic explorations into the roles of smoke in everyday life, through fieldwork suspension, and contextualised COVID-19 response. These experiences demonstrate how a basis of reflexive ethnographic engagement with communities can underpin thoughtful responses to upcoming challenges, with implications for future “global health” work, both within and beyond the pandemic context.